Low-dose urokinase thrombolytic therapy for patients with acute intermediate-high-risk pulmonary embolism: A retrospective cohort study. - Cuilian Weng; Xincai Wang; Long Huang; Xingsheng Lin; Qinghua Liu (PLoS ONE)
Introduction Patients at intermediate-high risk of developing a pulmonary embolism (PE) are very likely to experience adverse outcomes, such as cardiovascular instability and death. The role of thrombolytic therapy in intermediate-high-risk PE remains controversial. Objectives This study aimed to determine the efficacy and safety of low-dose urokinase (UK) thrombolytic therapy for intermediate-high-risk PE. Patients and methods This retrospective study included 81 consecutive patients with intermediate-high-risk PE from two centers. Patients received low-dose UK or low-molecular-weight heparin (anticoagulant therapy group). The efficacy outcomes were mortality, computed tomography pulmonary angiography (CTPA)-confirmed absorption, and dyspnea. Safety was assessed as the incidence of bleedings. Results The in-hospital mortality, 9-month mortality, and long-term mortality at the last follow-up were comparable for the low-dose UK group and the anticoagulant therapy group (6.45% vs. 0%, p = 0.144, 9.68% vs. 8.16%, p = 0.815, and 12.90% vs. 12.24%, p = 0.931, respectively). CTPA-confirmed absorption at one month after admission was higher in the low-dose UK group than in the anticoagulant therapy group (p = 0.016). The incidences of short-term dyspnea at discharge and long-term dyspnea at the last follow-up were lower in the low-dose UK group than in the anticoagulant therapy group (27.59% vs. 52%, p = 0.035, 33.33% vs. 58.14%, p = 0.043, respectively). No major bleeding occurred. The incidence of minor bleeding was not significantly different between the two groups (3.23% vs. 6%, p = 0.974). Conclusion In intermediate-high-risk PE, a low-dose UK might increase CTPA-confirmed absorption and improve short-term and long-term dyspnea without affecting mortality or increasing the bleeding risk.